Cavitation and erosion wear resistance of carbon structural steels - Skyba, M.Ye.; Oleksandrenko, V.P.; Stechyshyn, M.S.; Martynyuk, A.V. (Problems of Tribology, 2019)
In the paper, based on the analysis of literary sources and own researches of authors, the results of cavitation and erosion wear resistance of structural steels are systematized depending on their thermal processing (structure) and type of environment.The structural structure of steels is based on the analysis of wear resistance during cavitation and erosion fracture of surfaces, and the mechanisms of cavitation fracture of dodectoid, zavectotoid and perlite steels are considered.Destruction of dodectoid steels begins with ferrite, and then extends to perlite grains. The wear resistance of the pearlite grains of the plate-shaped form is higher than that of perlite of the granular form. Cavitation wear resistance of zeutectoid steels is determined mainly by the properties of perlite. The mechanical properties of which depend on the dispersion and shape of the particles of cementite.In perlite steels, reducing the size of its grain increases their erosion resistance, especially in the presence of cementite in the structure of the grid, and not ferrite grids.Using different types of thermal and thermocyclic heat treatment, it is possible to form appropriate structures and, accordingly, increase the cavitation and erosion wear resistance.